The compensation committee handbook - Reda, James F.; Reifler, Stewart; Stevens, Michael L. (Hoboken, New Jersey : Wiley, 2014)
"New and updated information on the laws and regulations affecting executive compensationNow in a thoroughly updated Fourth Edition, The Compensation Committee Handbookprovides a comprehensive review of the complex issues challenging compensation committees that facerevised executive compensation disclosure regulations issued by the SEC, as well as GAAP andIFRS rulings and trends. This new and updated edition addresses a full range of functionalissues facing compensation committees, including organizing, planning, and best practicestips. Looks at the latest regulations impacting executive compensation, including new regulationsissued by the SEC, as well as GAAP and IFRS rulings and trends Covers the selection and training of compensation committee members Explores how to make compensation committees a performance driver for a company Guides documentation requirements and timing issues The Compensation Committee Handbook, Fourth Edition will help all compensationcommittee members and interested professionals succeed in melding highly complex technical informationand concepts with both corporate governance principles and sound business judgment"--
Includes bibliographical references.
Print version record and CIP data provided by publisher.
Keywords: Compensation management -- United States -- Handbooks, manuals, etc; Wages -- Law and legislation -- United States -- Handbooks, manuals, etc; BUSINESS & ECONOMICS -- Strategic Planning; Compensation management; Wages -- Law and legislation; United States; Electronic books; Handbooks and manuals